Dual-source CT coronary angiography: Effectiveness of radiation dose reduction with lower tube voltage - Sabarudin, A.; Yusof, A.; Tay, M.; Ng, K.; Sun, Zhonghua (Oxford University Press, 2013)
This study was conducted to investigate the effectiveness of dose-saving protocols in dual-source computed tomography (CT) coronary angiography compared with invasive coronary angiography (ICA). On 50 patients who underwent coronary CT angiography was performed dual-source CT (DSCT) and compared with ICA procedures. Entrance skin dose (ESD), which was measured at the thyroid gland, and effective dose (E) were assessed for both imaging modalities. The mean ESD measured at the thyroid gland was the highest at 120 kVp, followed by the 100 kVp DSCT and the ICA protocols with 4.0±1.8, 2.7±1.0 and 1.1±1.2 mGy, respectively. The mean E was estimated to be 10.3±2.1, 6.2±2.3 and 5.3±3.4 mSv corresponding to the 120-kVp, 100-kVp DSCT and ICA protocols, respectively. The application of 100 kVp in DSCT coronary angiography is feasible only in patients with a low body mass index of <25 kg m−2, which leads to a significant dose reduction with the radiation dose being equivalent to that of ICA.